Merkel cell carcinoma. Case report - Pink, Richard; Molitor, Martin; Ehrmann, Jiri; Tvrdy, Peter; Michl, Petr; Pazdera, Jindrich (Biomedical papers, 2014)
Background: Merkel cell carcinoma (MCC) is a rare aggressive skin tumour affecting mainly older and immuno suppressed individuals (see our review on MCC in this volume).Aim: This is a case report describing our first experience with Merkel cell carcinoma in an elderly woman on chemo therapy for lymphoma and it covers the diagnosis, treatment and outcome.Methods: We did a radical excision of the soft tissue in the tumor area in conjunction with total paroditectomy and resection of the body of the zygomatic bone by radical block neck dissection. The skin defect was reconstructed myocutaneous free flap by a plastic surgeon.Results and Conclusion: At 12 months follow-up, the MCC had not recurred.
Keywords: merkel cell carcinoma; immuno supression; diagnosis; treatment